PERFIL EPIDEMIOLÓGICO E MICROBIOLÓGICO DE PACIENTES COM OSTEOMIELITES EM UM SERVIÇO DE REFERÊNCIA NO ESTADO DO ESPÍRITO SANTO ENTRE 2017 E 2019 - Xavier, Carolina Salume (2022)
Abstract Introduction: One of the most challenging complications of trauma surgery is infection after fracture fixation (IAFF), whose early diagnosis and proper management is essential for the prevention of chronic osteomyelitis, which has increased globally over the years. The increasing occurrence of traffic accidents which lead to high-energy traumas and complex open fractures, is a factors that contributes to the this rising number. The higher frequency of multidrug- resistant microorganisms makes treatment even more challenging and a multidisciplinary team including orthopedic surgeons and infectious disease specialists is necessary to manage the cases properly. Objective: Describe the epidemiological and microbiological profile of patients with osteomyelitis assisted at Hospital Dório Silva (HDS) between 2017 and 2019, and their clinical outcome evaluated 12 months after surgical treatment. Methods: A case series study of patients diagnosed with osteomyelitis assisted at HDS was conducted, evaluating clinical-demographic variables, microorganisms identified in cultures of bone fragments and clinical outcome 12 months after treatment was completed. Results: One hundred and seventy- nine patients were included in the study. Most patients were male (n = 128; 71.5%) and diagnosed with chronic osteomyelitis (n = 169; 94.4%). One hundred and thirty-seven of the osteomyelitis cases were caused by a single bacterial agent (76.6%), and 42 (26.47%) were polymicrobial. One hundred and forty patients (78.2%) presented with recurrence of osteomyelitis. The most prevalent pathogens identified were gram-positive cocci, Staphylococcus aureus (n = 104; 37.4%) and coagulase-negative Staphylococcus (n = 52; 18.7%) followed by gram-negative bacteria (n = 109; 39.2%.). Conclusion: The epidemiological and microbiological profile found in this study is similar to the current literature, and have shown a highest prevalence of chronic post-traumatic osteomyelitis of the lower limb among men over 50 years old, and infections by gram-positive cocci, but with a higher proportion of recurrences. It points out to the importance of elucidating the risk factors that lead to recurrence of the infection, as well as structuring health centers compound by an integrated multidisciplinary team to assist patients with orthopedic fractures and consequent bone infections.